Kejenuhan dan Motivasi Belajar dengan Prestasi Akademik - Afifah Khoirunnisa; Muhamad Uyun (LPPM Universitas Abdurrab, 2024)
This research aims to determine the relationship between learning boredom and learning motivation and academic achievement. The subjects of this research were 122 students from the class of 2020, Faculty of Psychology, UIN Raden Fatah Palembang. The number of subjects (112 women and 10 men) aged 20-23 years. Determining research subjects used the purposive sampling method. This research uses quantitative research methods with multiple regression techniques, as well as data collection using a learning boredom scale and a learning motivation scale. The results of the analysis show: 1) There is a relationship between learning boredom and learning motivation with academic achievement with a significance level of 0.047 (p<0.05). 2) There is no relationship between boredom and academic achievement with a significance level of 0.187 (p>0.05). 3) there is a relationship between learning motivation and academic achievement with a significance value of 0.032 (p<0.05). This research shows that learning boredom and learning motivation together have a relationship with academic achievement. Of the two independent variables, the learning boredom variable has no relationship with academic achievement. Meanwhile, the learning motivation variable is related to academic achievement. The implementation of this research is to produce innovative learning interventions and strategies that focus on increasing learning motivation and reducing learning boredom in students.